Simonides of Ceos and poetry as téchne (2012)
The platonic “explanation” concerning poetic creation in the dialogue Ion, which explains poetry as an effect of inspiration, allows us to identify the cultural conditions that underlie this conception; due to a lack of writing the entire Greek wisdom, in